Luce Fabbri on het 90th birthday. F.l.t.r: Laudi, Gallegos (Beto), Rago, Céspedes, Ribeiro. In front: Prieto, Luce, Errandonea, Martha
Luce Fabbri on het 90th birthday. F.l.t.r: Laudi, Gallegos (Beto), Rago, Céspedes, Ribeiro. In front: Prieto, Luce, Errandonea, Martha.